Traditional Games from Sentani Papua: Documentation and the Potentials of Utilization - Wigati Yektiningtyas; Siswanto NFN (Universitas Andalas, 2023)
The Sentani people in Papua have wealth of cultural heritages which was formerly actively practiced. One of them is traditional games (TG). Since 1970 when their area turned into a provincial capital and infrastructure development took place and modernization, the Sentani people began to lose land for TG. Now the younger generation does not recognize and practice these traditional sports and games. This study aims to (1) document traditional Sentani sports and games and (2) discuss their potential utilization in several fields. This research was conducted in October-December 2022 in several villages and islands on Lake Sentani through interviews and FGDs with informants consisting of tribal chiefs, the elders, Papuan customary council members, and government officials. This research found several TG which can be divided into two, namely water TG i.e., rukha hasai, rem phaeikho-phaeikho, and bhu phaeikho-phaeikho as well as land TG, i.e., mokhone oro habele sablei, fela-fela, and mendelauw. TG couldbe utilized as media of education, charater building, tourism and creative economy. Apart from being a social awareness, it is hoped that this research can become a cultural preservation of Sentani and utilized so that this intangible heritage does not become extinct and can be disseminated to the world community.